Morphology and molecular characterization of Demidospermus spirophallus n. sp., D. prolixus n. sp. (Monogenea: Dactylogyridae) and a redescription of D. anus in siluriform catfish from Brazil - Franceschini, L. [UNESP]; Zago, A. C. [UNESP]; Müller, M. I. [UNESP]; Francisco, C. J. [UNESP]; Takemoto, R. M.; Da Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2018)
The present study describes Demidospermus spirophallus n. sp. and Demidospermus prolixus n. sp. (Monogenea, Dactylogyridae) from the siluriform catfish Loricaria prolixa Isbrücker & Nijssen, 1978 (Siluriformes, Loricariidae) from the state of São Paulo, Brazil, supported by morphological and molecular data. In addition, notes on the circumscription of the genus with a redescription of Demisdospermus anus are presented. Demidospermus spirophallus n. sp. differed from other congeners mainly because of the morphology of the male copulatory organ (MCO), which exhibited 2 counterclockwise rings, a tubular accessory piece with one bifurcated end and a weakly sclerotized vagina with sinistral opening. Demidospermus prolixus n. sp. presents a counterclockwise-coiled MCO with 1 rings, an ovate base, a non-articulated groove-like accessory piece serving as an MCO guide, two different hook shapes, inconspicuous tegumental annulations, a non-sclerotized vagina with sinistral opening and the absence of eyes or accessory eyespots. The present study provides, for the first time, molecular characterization data using the partial ribosomal gene (28S) of two new species of Demidospermus from Brazil (D. spirophallus n. sp. and D. prolixus n. sp.), and Demidospermus anus from Loricariichthys platymetopon Isbrücker & Nijssen, 1979 collected in the Upper Paraná River floodplain, Brazil. Additionally, a revision of the species composition of this genus and others that occur in catfish is proposed to elucidate problems with their circumscription. The Brazilian species of Demidospermus clustered together as sister taxa among Neotropical dactylogyrids from siluriforms. The morphological characterization of D. spirophallus n. sp. and D. prolixus n. sp., and the molecular data of the three species in the present study will extend knowledge about this monogenean genus from the Neotropical region, and provide new information for future phylogeny studies.